Beispiel Nr: 16
$ \text{Gegeben:} \\ a1 \cdot x + b1\cdot y + c1\cdot z=d1\\ a2\cdot x + b2\cdot y + c2\cdot z=d2\\ a3\cdot x + b3\cdot y + c3\cdot z=d3\\ \\ \text{Gesucht:} \\\text{x,y,z} \\ \\ \textbf{Gegeben:} \\ 6 x +4 + 5 z=8\\ 4 x +2 y + 3 z=7\\ 5 x +3 y + 4 z=9\\ \\ \\ \textbf{Rechnung:} \\ 6 x + 4 y + 5 z=8\\ 4 x +2 y +3 z=7\\ 5 x +3 y +4 z=9\\ D_h=\left|\begin{array}{ccc} 6\ & 4 & 5\\ 4&2 & 3\\ 5& 3 & 4 \\ \end{array}\right| \begin{array}{cc} 6\ & 4 \\ 4&2 \\ 5& 3 \end{array} \\ D_h=6 \cdot 2 \cdot 4+4 \cdot 3 \cdot 5 +5 \cdot 4 \cdot 3 - 5 \cdot 2 \cdot 5 -6 \cdot 3 \cdot 3 -4 \cdot 4 \cdot 4=0 \\ D_x=\left|\begin{array}{ccc} 8\ & 4 & 5\\ 7&2 & 3\\ 9& 3 & 4 \\ \end{array}\right| \begin{array}{cc} 8\ & 4 \\ 7&2 \\ 9& 3 \end{array} \\ D_x=8 \cdot 2 \cdot 4+ 4 \cdot 3 \cdot 9 +5 \cdot 7 \cdot 3 - 5 \cdot 2 \cdot 9 - 8 \cdot 3 \cdot 3 -4 \cdot 7 \cdot 4=3\\ D_y=\left|\begin{array}{ccc} 6\ & 8 & 5\\ 4&7 & 3\\ 5& 9 & 4 \\ \end{array}\right| \begin{array}{cc} 6\ & 8 \\ 4&7 \\ 5& 9 \end{array} \\ D_y=6 \cdot 7 \cdot 4+8 \cdot 3 \cdot 5 +5 \cdot 4 \cdot 9 - 5 \cdot 7 \cdot 5 -6 \cdot 3 \cdot 9 -8 \cdot 4 \cdot 4=3 \\ D_z=\left|\begin{array}{ccc} 6\ & 4 & 8\\ 4&2 & 7\\ 5& 3 & 9 \\ \end{array}\right| \begin{array}{cc} 6\ & 4 \\ 4&2 \\ 5& 3 \end{array} \\ D_z=6 \cdot 2 \cdot 9+4 \cdot 7 \cdot 5 +8 \cdot 4 \cdot 3 - 8 \cdot 2 \cdot 5 -6 \cdot 7 \cdot 3 -4 \cdot 4 \cdot 9=-6\\ \\ L=\{\}$